SPECIFIC ASPECTS OF INTERACTION OF PLATELETS WITH THE HEPARINIZED MATERIALS - E.A. Nemets; V.I. Sevastianov; S.P. Uvarov; O.V. Romanov (Вестник трансплантологии и искусственных органов)
Comparative analysis of anticoagulant nature on medical materials testing was done. It was found that change of citrate by heparin is accompanied by significant changes in platelet adhesion and activation. This results allowed us to arrive at a conclusion about reasonability of heparin usage as anticoagulant in in vitro testing.